أثر الصادرات و الواردات علي النمو الاقتصادي دراسة قياسية علي الاقتصاد الليبي خلال الفترة(1970-2014) (Economic studies journal, 2019)
This study examines the impact of exports and imports on economic growth of the Libya economy over the period 1970-2014 by applying Johansen co-integration test and (VECM). The study found that there is co-integration between exports, imports, and economic growth; also, there is a short term relationship between the variables. Imports and exports in preview year have a negative impact on GDP. The reason for the GDP has negatively impacted by exports in the preview year may due to oil price fluctuations.
Keywords: Imports; exports; economic growth; Libya economy; Johansen Co-integration test; vector error correction model (VECM)